Commodities, Prices and Risk: The Changing Market for Non-Slave Products in Pre-Abolition West Africa - Angus Dalrymple-Smith; Pieter Woltjer (African Economic History Network (AEHN), 2016)
In this chapter, we have examined the changing market for African commodities in the decades before the British abolished their transatlantic slave trade. By constructing a new time series of the quantities and prices of goods imported from Africa in the customs ledgers we have shown that there was a far more substantial increase in the trade than the previous data suggested. Furthermore, we suggest that this was driven by slave traders and was primarily a phenomena of the Eastern and more specifically Biafran/Cameroonian region of the West African coast which was a significant reversal of the pattern of commodity trading until the 1770s. These traders also seem to have bought relatively fewer slaves while purchasing greater quantities of non-slave products. We hypothesise that this trend was driven by a number of different factors. Firstly, commodity prices were rising in Europe, while prices on the coast remained relatively stable, in marked contrast to slaves. In addition, the period saw increasing levels of risk and parliamentary legislation to reduce crowding on ships which may have further encouraged captains to purchase more commodities as a risk reduction, profit enhancing strategy.
Keywords: N17; N27; N37; 330; West Africa; trade; slaves; commodities